Impact of Insurance Risk Management on Fixed Capital Formation in Nigeria.: Array - Oluwaleye, Taiwo; Kolapo, Funso Tajudeen; Osasona, Adedeji Viscker (Acta Universitatis Danubius. Œconomica, 2022)
This study investigated the impact of insurance risk management on fixed capital formation in Nigeria. The study sampled all insurance companies operating in Nigeria. Time series data covering the period 1996 - 2019 were obtained from the CBN Statistical Bulletin, Annual Report of National Insurance Commission, and the various issues of the Nigerian Stock Exchange Factbook. General business insurance and life insurance claims were used to represent risk management (independent variable), while gross capital formation was used as the dependent variable. Data were analyzed using descriptive statistics, unit root, Auto-Regressive Distributed Lag (ARDL) and ARDL Bound cointegration test as well as a model diagnostic test by Stata 15 software. The study found that life insurance claims exert an insignificant positive impact on gross capital formation, with the reported estimate (p=0.058 >0.05), general insurance business exerts an insignificant negative impact on gross fixed capital formation, with an estimate (p= 0.065>0.05) and the non-existent of long-run connection between gross fixed capital formation and independent risk management. Our study suggests that regulatory authorities should implement strategies to encourage Nigerians to patronize life insurance companies, since this would lead to greater insurance investment and, in turn, growing in Nigeria's gross capital formation, among other things.